A Memorial of Joseph Henry - United States. Congress; Smithsonian Institution (1880)
A memorial written for Joseph Henry, who served as secretary for the National Institute for the Promotion of Science, the precursor of the Smithsonian Institution, and then became the first Secretary of the Smithsonian Institution. As a scientist, he made significant discoveries in electromagnetism including the electromagnetic phenomenon of self-inductance as well as developing the electromagnet into a practical device. The frontispiece portrait of Henry, cover and title page have been digitized from this work.
Keywords: Electromagnetism; National Institute for the Promotion of Science; Self-inductance; Smithsonian Institution; Henry, Joseph, 1797-1878